1996
DOI: 10.1139/v96-258
|View full text |Cite
|
Sign up to set email alerts
|

Steric effects of bulky phosphines on 95Mo NMR shieldings

Abstract: Three sets of substituted molybdenum carbonyl complexes of the type Mo(CO)~,(PY,), (n = 1-3) with a wide range of phosphorus ligands (Y = Ar, R, OR, NR,, C1, H) were synthesized and their respective 9 s~o NMR spectral data were collected, The steric effect of PY, plays an unexpectedly important role in the paramagnetic shielding term determining E(~'Mo), and is even observed in the least crowded M(CO),(PY,) complexes. It is deduced that the steric requirement reduces the commonly accepted a-ability of phosphit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…It is reported that some broad bands around 2000 cm À1 indicated Mo(CO) 6Àx L x species (where L ¼ solvent, such as i-propanol). 32 For the as-prepared sample at 100 C (Fig. 7a), the broad bands around 2000 cm À1 were obviously distinguishable.…”
Section: Resultsmentioning
confidence: 93%
“…It is reported that some broad bands around 2000 cm À1 indicated Mo(CO) 6Àx L x species (where L ¼ solvent, such as i-propanol). 32 For the as-prepared sample at 100 C (Fig. 7a), the broad bands around 2000 cm À1 were obviously distinguishable.…”
Section: Resultsmentioning
confidence: 93%
“…It is interesting that cis ‐[Mo(CO) 4 {κ 2 ‐ P , P ‐( L2 )}], 2a , undergoes CO elimination at ambient temperature because (1) typically [Mo(CO) 3 L 3 ] complexes are formed via a trisubstituted intermediate {[Mo(CO) 3 DMF 3 ] or [Mo(CO) 3 (NCMe) 3 ], } or (2) can be synthesized from [Mo(CO) 6 ] through photolysis. Either method requires high temperatures, and/or extended reaction times , . To the best of our knowledge the only other example of CO elimination from a group VI tetracarbonyl complex is with the multi/hetero‐donor ligand, Ph 2 P( o ‐C 6 H 4 )CH=N(CH 2 ) 2 ( o ‐C 5 H 4 N), (PNN) .…”
Section: Resultsmentioning
confidence: 99%
“…From this, the main effects of each variable ( a P and a T ) and an interaction term ( a PT ) are obtained. Mathematica was used to solve the system of equations and generate response surfaces …”
Section: Methodsmentioning
confidence: 99%
“…In the early stages of the development of the QALE model (quantitative analysis of ligand effects), we also proposed that PCl 3 is a pure σ donor . The problem with empirical studies is that the total electron donor capacity of PZ 3 is the result of the combination of at least two electronic properties (σ donicity and π acidity) when PZ 3 is bonded to a transition metal. ,,,,,,, No method has been found to separate these electronic effects when only the properties of transition-metal complexes are considered.…”
Section: Introductionmentioning
confidence: 99%